كوالێتی ژیان ڕەهەندو پێكهاتەكانی - عبداللە, پ.د.ئاسۆ ابراهیم; ابراهیم, م.م.لانە ئاراس (Sulaimani Journal for Humanities, 2023)
The Quality of life is one of the relatively modern concepts at the level of its scientific uses, as researchers have paid attention to it in their studies The history of the emergence of the quality of life and its origins dates back to the eighteenth century until now. And interest in the various aspects of life, self -fulfillment and happiness has become one of the basic necessities as a starting point for obtaining material and moral needs from Society Members. And as a factor that directly influences the continuity of community life and as a means of development that all society seeks, in this context we present in our research ideas and scientific proposals related to the concept of quality of life in a historical context and determine its dimensions and components from a social perspective.